Effect of Lactobacillus casei FNCC 0090 to improve gastrointestinal bacterial abundance, immune system and water quality in catfish farming - NURUL ‘AINI; MUHAMMAD BACHRUDDIN; FATIMAH FATIMAH; SAPTO ANDRIYONO; SRI PUJI ASTUTI WAHYUNINGSIH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. ‘Aini N, Bachruddin M, Fatimah, Andriyono S, Wahyuningsih SPA. 2024. Effect of Lactobacillus casei FNCC 0090 to improve gastrointestinal bacterial abundance, immune system and water quality in catfish farming. Biodiversitas 25: 2130-2138. Catfish is the most widely cultivated type of fish. However, along with the increase in catfish production as an effort to fulfill the fishery stock, there is an obstacle to the emergence of disease infection caused by Aeromonas hydrophila. For this reason, good fisheries management is required. One of the efforts to deal with this is by giving probiotics Lactobacillus casei FNCC 00990. Lactobacillus casei FNCC 0090 is expected to improve the immune system of catfish through improving the blood profile of fish and increasing the number of lactic acid bacteria in the gastrointestinal tract of catfish. This research aims to determine the effect of administering the probiotic L. casei FNCC 0090 on the abundance of microbes in the fish digestive tract, immune system, and water quality in cultivating catfish infected with A. hydrophila. The research design was a completely randomized design with five treatments and five replications. The treatments were A (administering 5% probiotics and infected with 0.1 mL x 108 CFU/mL), B (10% probiotics and infected), C (15% probiotics and infected), KP (positive control with 0% probiotics and infected with pathogens), KN (negative control, without probiotics and pathogen infection). Fish are kept for 42 days; on the 35th day, the fish were infected with A. hydrophila by intramuscular injection. Probiotics were mixed with feed with a total of 108 CFU/mL. Data in the form of BAL counts and total bacterial counts of fish digestive tracts, blood profiles, and water quality were analyzed using Statistical Package for the Social Sciences (SPSS) software version 23.0 (IBM SPSS Statistics). The results showed